P2X1-initiated p38 signalling enhances thromboxane A2-induced platelet secretion and aggregation - Huang, Zhangsen; Liu, Pu; Zhu, Linjing; Li, Nailin; Hu, Hu (Thrombosis and Haemostasis, 2014)
ATP released by activated platelets can serve as a positive feedback machinery to amplify platelet responses by activating P2X1 receptors. It has, however, not been defined how P2X1 activities influence thromboxane A2 (TXA2)-stimulated platelet functional responses. Our aim was to elaborate the molecular mechanisms of P2X1 engagements in TXA2-induced platelet secretion and aggregation. P2X1 inhibition by 1 µM NF449 inhibited platelet P-selectin expression induced by a low concentration of the TXA2 analogue U46619 (0.3 µM) (32.0 ± 2.0% vs 43.4 ± 3.0%; n=5; p<0.05). p38 inhibition by SB203580, but not ERK inhibition by U0126, elicited a similar inhibition by NF499. The combination of NF449 and SB203580 provided, however, no additive effects. U46619-induced platelet aggregation was similarly decreased by NF449 and SB203580 alone or incombination, and by P2×1 pre-desensitisation with α,β-Me-ATP. U46619 caused rapid and reversible P2×1-dependent p38 phosphorylation. However, the P2X1-p38 pathway mainly enhanced mild platelet activation by U46619, because α,β-Me-ATP supplementation or p38 blockade had no effect on intense platelet activation induced by a higher concentration of U46619 (3 µM). In conclusion, P2×1 activation, via p38 signalling, potentiates platelet activation initiated by low doses of U46619. Hence, the P2X1-induced p38 signalling promotes more robust platelet activation in response to mild platelet stimuli.
Keywords: Platelets; ATP; P2X1; p38; thromboxane A2